(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
This article provides a broad overview of the role of financial mechanisms—particularly green bonds and international grants—in the transition to a green economy. Green financing is evaluated as a key tool for ensuring ecologically sustainable development in the modern economy. By comparing global and Uzbek experiences, the author analyzes the advantages, practical applications, and challenges of these financial tools. Additionally, the formation of the green bond market, grant allocation mechanisms, and cooperation with international organizations are discussed. The article concludes with recommendations for developing the green economy. This research has scientific and practical significance and substantiates the importance of economic approaches toward ecological sustainability.